Rdzogs pa chen po ka dag raṅ byuṅ raṅ śar gyi brgyud paʼi gsol ʼdebs bźugs so (s.n., 1970)
Devotional verses in praise of teachers in a transmission lineage of Dzogchen precepts of the Nyingmapa sect.